2010
DOI: 10.1136/aim.2009.001651
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Self-Report of Acupuncture Needle Sensation during Deep Needling with Bi-Directional Rotation

Abstract: Background Traditionally, acupuncturists manipulate needles to enhance sensations referred to as de qi or 'acupuncture needle sensation'. Acupuncture needle sensations are complex and quantifying the experience has been diffi cult. The aim of this crossover study was to measure self-reported needle sensation during deep and bi-directional rotated needling in 15 healthy volunteers. Methods Each participant received an experimental intervention consisting of superfi cial needling followed by deep needling and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
(29 reference statements)
1
30
0
2
Order By: Relevance
“…However, several clinical trials have shown that real acupuncture needling, especially with rotation, can elicit higher intensity sensations than sham or superficial needling. 5,7,21,23,27 Our observed rate of complete recovery in the control group (77.1% of patients) is similar to that in the corticosteroid group (76.7%) in a recent Cochrane review, 28 which suggests that patients in our control group had similar experiences to patients who received sham acupuncture.…”
Section: Limitationssupporting
confidence: 60%
See 2 more Smart Citations
“…However, several clinical trials have shown that real acupuncture needling, especially with rotation, can elicit higher intensity sensations than sham or superficial needling. 5,7,21,23,27 Our observed rate of complete recovery in the control group (77.1% of patients) is similar to that in the corticosteroid group (76.7%) in a recent Cochrane review, 28 which suggests that patients in our control group had similar experiences to patients who received sham acupuncture.…”
Section: Limitationssupporting
confidence: 60%
“…[6][7][8][9][10][11] However, this long-held belief has not been confirmed by sufficient evidence from randomized controlled trials. 5 Consequently, de qi and its related techniques have been neglected in acupuncture practice and research. As such, the therapeutic effects of acupuncture may be seriously compromised.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…22 Participants may have used the sensations generated by the real and sham needles as cues for making their judgements. Benham et al 23 found that deep needle insertion produced a higher intensity of needle sensation compared with superfi cial insertion. In our study, the needle insertion depth for the upper limb acupoints was more superfi cial than the lower limb acupoints.…”
Section: Limitationsmentioning
confidence: 99%
“…This might explain the spread of needle de q' sensations away from the needle. 26 Interestingly, our research found that needle sensation distribution patterns were markedly similar to trigger point referral patterns, leading us to speculate that needle stimulation may be affecting the same structures as those affected when stimulating trigger points 25 …”
mentioning
confidence: 97%